The splenic Littoral cell angioma in China: a case report and review - Hu Zong-Qiang; A Yong-Jun; Sun Qiang-Ming; Li Wen; Li Li (World Journal of Surgical Oncology, 2011)
Abstract Littoral cell angioma (LCA) is a rare splenic vascular neoplasm that arises from the cells lining the red pulp sinuses. It is deemed to be a benign and incidental lesion. The earliest literature report of littoral cell angioma has been described by Falk. The examination of samples after splenectomy reveals similar pathological change and its change rule is summarized. However, many recent reports have described it to be a malignant tumor with congenital and immunological associations. Generally speaking, the definitive diagnosis can only be made after histological and immunohistochemical profiles. In this case report, we presented the case of a 48-year-old woman with multiple splenic LCAs. Initially, the patient was characteristics of abdominal distension, weakness and fatigue. Multiple hemangiomas were observed in the spleen through abdominal ultrasonic diagnosis. Computed tomography (CT) scans revealed the splenomegaly with multiple round and hyperdense lesions. The patient subsequently underwent splenectomy. Postoperative histological and immunohistochemical studies confirmed the diagnosis of LCA. Based on the presentation of this case, clinical, radiographic and pathological results of LCA as well as recent advances in our understanding of this uncommon splenic lesion were reviewed. LCA is an uncommon splenic tumor diagnosed in patients with or without abdominal discomfort. Only a few case reports regarding this kind of tumor have been published as inconsistent results. In the present paper, we have reported a case of LCA and reviewed the literature.